RIPPA: Identification of MHC‐II Binding Peptides from Antigen Using a Yeast Display‐Based Approach. Issue 1 (18th January 2022) - Liu, Rongzeng; Jiang, Wei; Li, Ying; Mellins, Elizabeth D.
Abstract: Mapping MHC‐II binding peptides derived from an antigenic protein for potential CD4+ T‐cell epitopes has been challenging due to a lack of experimental approaches that are both quantitative and rapid. The rate‐limiting steps in current approaches include the construction of single MHC allele expressing cell lines and/or the purification of the MHC‐II allelic proteins for peptide elution (i.e., mass spectrometry) or in vitro peptide binding (i.e., ELISA) assays. These labor‐intensive steps typically take up to 4 months or more. In this protocol, we describe a system that uses yeast cells to display "empty" (i.e., without covalently linked peptides) MHC‐II heterodimers that are capable of binding exogenously added peptides of interest. This yeast‐MHC‐II system eliminates the time‐consuming soluble MHC‐II purification steps, allowing rapid identification of peptide ligands from protein antigens (RIPPA). The amount of peptide loading to MHC‐II or the extent of competition between indicator and competitor peptides at the surface of yeast cells can be quantitatively determined using flow cytometric analysis. Importantly, the protocol only takes ∼1 month from the construction of plasmids and the yeast display of "empty" MHC‐II to the quantitative determination of MHC‐II binding peptides from a given antigen. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Yeast display of "empty" MHC‐II Support Protocol : Construction of yeast shuttle vector expressing "empty" MHC‐II Basic Protocol 2 : Peptide competition on the surface of yeast cells Alternate Protocol : RIPPA in a 96‐well format